Novel Experiment for Scaled Power Flow Studies Towards Next-Generation Pulsed Power - Mundy,T; Bland,S; Lebedev,S; Chittenden,J; Marrow,K; Suttle,L; Halliday,J; Rose,C (2023)
In order to develop a better understanding of current losses in the magnetically insulated region of high-power pulsed power machines, it is crucial to be able to conduct experiments at scale in smaller facilities. Here, we present a novel experiment that has been tested on the MAGPIE driver at Imperial College. The targets are inexpensive and easy to customize for experiments ranging from power flow to warm dense matter. Simulations in COMSOL indicated electric fields of up to 600 MV/m and magnetic fields of up to 300 T could be produced on MAGPIE. In initial testing, Electric fields exceeding 100 MV/m and magnetic fields exceeding 50 T were generated, and both magnetically insulated transmission and plasma-shorted transmission were demonstrated.